Twenty-four-month outcomes from a cluster-randomized controlled trial of extending antiretroviral therapy refills in ART adherence clubs - Cassidy, T; Grimsrud, A; Keene, C; Lebelo, K; Hayes, H; Orrell, C; Zokufa, N; Mutseyekwa, T; Voget, J; Gerstenhaber, R; Wilkinson, L (Wiley, 2020)
Introduction: The antiretroviral therapy (ART) adherence club (AC) model has supported clinically stable HIV patients’ retention with group ART refills and psychosocial support. Reducing visit frequency by increasing ART refills to six months could further benefit patients and unburden health systems. We conducted a pragmatic non-inferiority cluster randomized trial comparing standard of care (SoC) ACs and six-month refill intervention ACs in a primary care facility in Khayelitsha, South Africa.